PRODUCTION ANALYSIS IN CORN AND COWS FARIMING IN KUBU RAYA REGENCY - Sinambela, Suiranto; Kusrini, Novira; Imelda, Imelda (Jurnal Sains Mahasiswa Pertanian, 2019)
ABSTRACTCorn and cows are agricultural commodities that can compete in the market, and can create employment opportunities and income for farmers through the production cycle. This study aims to analyze the factors that influence production on corn and cows farming in Kubu Raya Regency. The analytical method used in this study is multiple regression analysis using the Cobb-Douglas production function equation and using the Ordinary Least Square (OLS) regression equation. In sweet corn farming, the results of data processing show that the adjusted-R2 value of 96.57% of production is influenced by the seven variables used in this study, the remaining 3.43% are influenced by other variables outside the regression model. In beef cows farming, the results of data processing show the adjusted-R2 value of 98.83% of the production is influenced by the six variables used in this study, the remaining 1.17% are influenced by other variables, excluding the regression model.Keywords: Cobb-Douglas Production Function, . Corn Farming, Cows Farming, Production Factors